PENGARUH PENGELUARAN PEMERINTAH, PRODUKTIVITAS TENAGA KERJA DAN FAKTOR DEMOGRAFI TERHADAP KINERJA PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA PROVINSI MALUKU - Mohammad Ratmasa Serang (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
Human development according to UNDP (United Nation Development Program) is a process to expand choices for the population. When referring to this definition, the population becomes the ultimate goal of development, while the development effort is a means (principal means) for that purpose. Human development achievements in Maluku Province are low compared to Indonesia's human development index. In general, research aims to optimize the achievement of human development performance by looking for determinants / determinants that affect the performance of human development in the district / city of Maluku Province. Specifically this study aims to 1) analyze partially the effect of government expenditure (economic expenditure) on human development performance 2) partially analyze the effect of government health-education expenditure, 3) analyze partially the effect of labor productivity level on human development performance and 4 ) partial analysis of the influence of demographic factors represented by the number of population on the performance of human development in the district / city of Maluku Province 2009-2014. The analytical method used is qualitative descriptive and quantitative analysis. The quantitative analysis tool used is the Data Panel regression model for secondary data of districts / cities in Maluku Province for the period 2009-2014. There are several approaches to estimating the panel data regression model, so it is necessary to conduct a series of statistical tests to obtain the most efficient and best regression parameters (BLUE, Best Linear Unbiased Regression). The stages of statistical testing include: First stage, Testing estimation models using Restricted F-Test, LM Test and Hauman Test, Second stage, testing violations of classical assumptions.